KEWENANGAN POLISI KEHUTANAN DALAM BIDANG PERLINDUNGAN HUTAN PADA PEMERINTAH DAERAH DI SULAWESI TENGAH - Ridholof, Hermanus (Katalogis, 2016)
It was a legal normative research adopting a number of theories (Theory of Authorities, Theory of Sovereignty, Theory of Legal Extentsion and Preference, Decentralization Principle, Devolution Principle and Good Governance Principle) and prevailing laws and regulations. The legal materials adopted in the researc were from bibliographical studies comprising primary, secondary and tertiary legal material. With reference to the research finding, it was foud that there was a breach or incompliance againt the lawsÂ  in the application of regulations in the governance of forest protection by provincial/regency/city goverments concerning the authorities of Forest Ranger in Central Sulawesi Province as the Forest Ranger is still under the control of Structural Officer of Echelon IV (Forest Protection Officer). Based on the normative overview, it was foud that from the very first time there had been a separation of authorities between those two government officer. The law provides that special police functions are attributes of authority that cannot be delegated and under the control of Minister of Environment whwn viewed from functional command hierarchy pertaining to be absolute governmental afffairs. On the other hands, the forest protection organization and its activities are included as concurrent governm,ent affairs, forest ptotrction sub-section, that can be delegated to relevant Governor and further delegated to relevant administration workong unit based on deconcentration principle.